Low power steam turbine energy efficiency and losses during the developed power variation - Mrzljak, Vedran (Array, 2018)
This paper investigates low power marine steam turbine during the variation in its developed power. The turbine is used for the Main Feedwater Pump (MFP) drive. Energy analysis of the Main Feedwater Pump Turbine (MFPT) is based on the measurements performed in nine different operating regimes. The measured operating parameters were steam pressure and temperature at the turbine inlet, steam pressure at the turbine outlet, and a water volume flow through MFP. Turbine energy power losses are most influenced by steam mass flow through the turbine and by steam specific enthalpy at the turbine outlet. An increase in turbine developed power causes a continuous increase in turbine energy efficiency. Analyzed turbine is balanced as most of the other steam system components – maximum energy efficiency will be obtained at the highest load, on which the majority of turbine and system operation can be expected during exploitation.